Transcriptionally regulated cell adhesion network dictates distal tip cell directionality. Issue 8 (26th May 2014) - Wong, Ming‐Ching; Kennedy, William P.; Schwarzbauer, Jean E.
<x xml:space="preserve">Abstract</x> Background: The mechanisms that govern directional changes in cell migration are poorly understood. The migratory paths of two distal tip cells (DTC) determine the U‐shape of the C. elegans hermaphroditic gonad. The morphogenesis of this organ provides a model system to identify genes necessary for the DTCs to execute two stereotyped turns. Results: Using candidate genes for RNAi knockdown in a DTC‐specific strain, we identified two transcriptional regulators required for DTC turning: cbp‐1, the CBP/p300 transcriptional coactivator homologue, and let‐607, a CREBH transcription factor homologue. Further screening of potential target genes uncovered a network of integrin adhesion‐related genes that have roles in turning and are dependent on cbp‐1 and let‐607 for expression. These genes include src‐1/Src kinase, tln‐1/talin, pat‐2/α integrin and nmy‐2, a nonmuscle myosin heavy chain. Conclusions: Transcriptional regulation by means of cbp‐1 and let‐607 is crucial for determining directional changes during DTC migration. These regulators coordinate a gene network that is necessary for integrin‐mediated adhesion. Overall, these results suggest that directional changes in cell migration rely on the precise gene regulation of adhesion. Developmental Dynamics 243:999–1010, 2014. © 2014 Wiley Periodicals, Inc.